Low levels of sulphur dioxide contamination of Venusian phosphine spectra. Issue 2 (30th May 2022) - Greaves, Jane S; Rimmer, Paul B; Richards, Anita M S; Petkowski, Janusz J; Bains, William; Ranjan, Sukrit; Seager, Sara; Clements, David L; Silva, Clara Sousa; Fraser, Helen J
ABSTRACT: New analysis is presented of the 1.1 mm wavelength absorption lines in Venus' atmosphere that suggested the presence of phosphine. We retrieve a sulphur dioxide observation from the JCMT archive that was simultaneous within a few days of the PH3  1-0 spectrum obtained in 2017 June, and demonstrate via a radiative transfer calculation that contamination of PH3  by SO2  was ≈10 per cent. We also present ALMA 2019 spectra of PH3  1-0 and an SO2  transition acquired simultaneously, and infer that SO2  line-contamination was ≲2 per cent (for the least-noisy half of the planetary disc). The contamination-subtracted ALMA and JCMT spectra (of 6–8σ sigma confidence) are now consistent with similar absorption-depths at the two epochs. The two values span −1.9(±0.2) 10 −4 of the continuum signal (which was re-estimated for ALMA), albeit for differing planetary areas. This suggests that the abundance attributed to phosphine in Venus' atmosphere was broadly similar in 2017 and 2019.